The Role of Job Satisfaction as a Mediator of the Relationship Between the Work Environment on Performance - Fathiya Aliyadanti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The company’s success in improving company performance is very dependent on the quality of the human resources that work within it. The role of human resources in company performance is very important, decisions taken by human resource managers are able to increase efficiency and provide increased company results, which also have an impact on employee performance. This research aims to examine the influence of the work environment on employee performance through job satisfaction as a mediating variable. The method used in this research is quantitative with Structural Equation Model-Partial Least Square (SEM-PLS) analysis of the SmartPLS program version 4.0. The population in this study was 140 employees of PT Angkasa Pura I Semarang Branch. The sampling technique in this research used a purposive sampling technique. The results of the analysis and hypothesis testing show that the work environment has no effect on employee performance. The work environment influences job satisfaction. Job satisfaction influences employee performance. The work environment influences employee performance through job satisfaction.